Education and the crime-age profile - Hansen, Kristine (The British journal of criminology, 2003)
That crime tends torise and peak in the mid to late teens and early twenties then declines with age has, by now, become an accepted fact. Despite this, over the last 20 years there have been numerous debates over the true nature of the relationship between crime and age. This paper uses self-report data collected from young males aged 16-25 in England and Wales to examine the crime-age profiles of two groups: those who leave school at 16 and those who stay on past the compulsory school leaving age. Findings show that for three categories of crime (property, handling and violent offences) the two groups have significantly different crime-age profiles. But that the gap between the two profiles can be accounted for by differences across the two groups in a number of observable variables related to the labour market, education, family, individual characteristics and the neighbourhood/area in which people live. The most important factors underpinning differences in the crime-age profiles by education group are whether an individual lives with their parents, family contact with the police and school truancy